Pharmacokinetics and Tolerability of Gemifloxacin (SB-265805) after Administration of Single Oral Doses to Healthy Volunteers - Allen, Ann (American Society for Microbiology, 2000)
Gemifloxacin (known as SB-265805 or LB-20304) is a potent, novel fluoroquinolone compound with a broad spectrum of antibacterial activity. The pharmacokinetics and tolerability of oral gemifloxacin were characterized in healthy male volunteers after a single dose of 20, 40, 80, 160, 320, 600, or 800 mg. Multiple serum and urine samples were collected and analyzed for gemifloxacin using high-performance liquid chromatography with fluorescence detection. Safety assessments included vital signs, 12-lead electrocardiogram readings, hematology, clinical chemistry, urinalysis, and adverse-experience monitoring. Gemifloxacin was rapidly absorbed after all doses. Maximum concentrations of gemifloxacin in serum (C(max)) were achieved approximately 1 h after dosing, after which concentrations in serum declined in a biexponential manner. Values of C(max) and the area under the concentration-time curve in serum from 0 h to infinity (serum AUC(0–∞)) increased linearly with dose. Serum AUC(0–∞) values (mean ± standard deviation) were 0.65 ± 0.01, 1.28 ± 0.22, 2.54 ± 0.31, 5.48 ± 1.24, 9.82 ± 2.70, 24.4 ± 7.1, and 31.4 ± 7.6 μg · h/ml following 20-, 40-, 80-, 160-, 320-, 600-, and 800-mg doses, respectively. The terminal phase elimination half-life was independent of dose, with an overall mean of 7.4 ± 2.0 h. The profiles indicated that the pharmacokinetic profile is suitable for a once-daily dosing regimen. Approximately 25 to 40% of the administered dose was excreted unchanged in the urine, and renal clearance (ca. 150 ml/min) was independent of dose. There were no significant changes in clinical chemistry, hematology, or urinalysis parameters, vital signs, or 12-lead electrocardiogram readings in subjects, irrespective of dose. The results of these studies support the further investigation of once-daily administration of gemifloxacin.